2022
DOI: 10.1039/d2ra05922c
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of NiFe alloys for efficient electrochemical hydrogen evolution reaction: effects of Ni/Fe molar ratios

Abstract: Developing and designing high-performance and stable NiFe electrodes for efficient hydrogen production in alkaline medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…The consistently lower Tafel slope values for FNC compared to NF can be attributed to the fact that the adsorption of H 2 O on Fe sites is more favourable than Ni, 59 which ultimately lowers the energy barrier for the Volmer step on FNC compared to the NF electrode. The Tafel slope values of FNC are comparable with previous studies on Fe/Ni based electrodes such as Chen et al , 60 where they reported Tafel slopes values of 161 mV dec −1 and 274 mV dec −1 for a nickel iron oxyphosphide (NiFeOP) and NiFe layered double hydroxide electrode, respectively, while Messaoudi et al 61 reported a Tafel slope of 179 mV dec −1 for a NiFe (3 : 1) alloy electrocatalyst. Chronoamperometric data in Fig.…”
Section: Resultssupporting
confidence: 87%
“…The consistently lower Tafel slope values for FNC compared to NF can be attributed to the fact that the adsorption of H 2 O on Fe sites is more favourable than Ni, 59 which ultimately lowers the energy barrier for the Volmer step on FNC compared to the NF electrode. The Tafel slope values of FNC are comparable with previous studies on Fe/Ni based electrodes such as Chen et al , 60 where they reported Tafel slopes values of 161 mV dec −1 and 274 mV dec −1 for a nickel iron oxyphosphide (NiFeOP) and NiFe layered double hydroxide electrode, respectively, while Messaoudi et al 61 reported a Tafel slope of 179 mV dec −1 for a NiFe (3 : 1) alloy electrocatalyst. Chronoamperometric data in Fig.…”
Section: Resultssupporting
confidence: 87%
“…The appearance of peaks (Ox) 2 /(Red) 2 before the onset potential of the OER present in the potential window of 1.2–1.5 V vs RHE is attributed to the β-Ni(OH) 2 /β-NiOOH transition. During the entire cycle run, the current of both redox features considerably increases, suggesting the oxidation of metallic Ni to Ni 2+ and further Ni 2+ to Ni 3+ according to eqs and , respectively Ni 0 + 2 OH Ni false( OH false) 2 + 2 e Ni false( OH false) 2 + OH NiOOH + H 2 normalO + e …”
Section: Resultsmentioning
confidence: 99%
“…To summarize, for OER, numerous Ni–Fe-based catalysts have been previously reported to improve the catalytic activity by several methodologies, , among which very few showed better activity under low-cost and energy-efficient conditions. Instead, most of them were reported to require costly materials, slugging methods, or external substrates to fabricate an efficient catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…These experimental parameters can be manipulated to control the structural, morphological, and electrocatalytic properties of the deposited material. It is well known that the electrocatalytic activity can be further improved by increasing the active surface area, electrochemical stability and electrical conductivity [33,34,35] . However, besides improving the electrocatalytic properties of MoS 2 deposits, little attention has been paid to tailoring the MoS 2 composition, structure and surface morphology for enhancing the HER kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the electrocatalytic activity can be further improved by increasing the active surface area, electrochemical stability and electrical conductivity. [33,34,35] However, besides improving the electrocatalytic properties of MoS 2 deposits, little attention has been paid to tailoring the MoS 2 composition, structure and surface morphology for enhancing the HER kinetics. Maximizing the utilization of the synergetic effect of Mo and S sites through the rational design of the MoS 2 structure is envisioned as a prominent but somewhat difficult and ill-defined approach to boost HER activity.…”
Section: Introductionmentioning
confidence: 99%